(untitled) (Journal of EAHIL, 2016)
For the first time a joint event between the library, the Medical Faculty and external partners was held at theÂ medical library of Bern University. With a combination of promotional and social activities and information skillsÂ taster sessions the library tried to raise awareness of e-resources and increase their use.